Always connected and always working? Some best practices for effective use of technology and electronic communication. - Christian K Hansen (Academic Chairpersons Conference Proceedings, 2015)
The presentation will cover best practices for overcoming challenges related to email security and privacy as well as the use of “profess-social” networking as a means for connecting with your students, alumni, industry and community and in promoting your department inside and outside your institution.
Keywords: email; social media; time management; electronic communication; security and privacy